ECONOMIC IMPACTS OF THE LAW OF CATTLE AND BEEF TRACEABILITY IN MARKETING CHANNELS ON THE DOMESTIC HANWOO BEEF INDUSTRY - 전상곤 (한국농촌경제연구원, 2010)
The purpose of this study is to evaluate the economic impacts of the Law of Cattle and Beef Traceability in marketing channels on the domestic Hanwoo beef industry. The Law of Cattle and Beef Traceability might affect the demand and supply of Hanwoo beef. After introducing the Law of Cattle and Beef Traceability into the marketing channels, the price of Hanwoo beef has increased a lot in the Korean beef market. Domestically produced Hanwoo beef has a price premium compared with the imported beef from foreign countries such as the U.S.A. or Australia. There had been an incentive for beef dealers in the domestic market to deceive the origin of the beef to capture the price premium. The Law of Cattle and Beef Traceability expanded into the marketing channel on June 22, 2009, which increased the demand for domestically produced Hanwoo beef. A simulation result shows that the increase of demand for Hanwoo beef would be 36.7 - 55.7 percent. The net impacts of the law are 38.7-57.8 percent increase in price and 16.4-21.7 percent increase in quantity.
Keywords: traceability; beef; Hanwoo; labelling; traceability; beef; Hanwoo; labelling